2019
DOI: 10.20899/jpna.5.2.134-154
|View full text |Cite
|
Sign up to set email alerts
|

Does Person-Organization Fit Mediate the Relationship between Affect-Based Work Antecedents and Public Employee Job Satisfaction?

Abstract: In this study we investigate whether person-organization fit mediates the relationship between affect-based work antecedents—specifically, transformational leadership and role clarity—and public employee job satisfaction. We hypothesize that transformational leadership and role clarity, as joint affect-based work antecedents, will trigger the effect of value congruence on job satisfaction in public organizations. Using a viewpoint survey of South Korean government officials, we estimate structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 79 publications
(116 reference statements)
3
9
0
1
Order By: Relevance
“…TL is found to positively affect POF, as indicated by a positive path coefficient value of 0.752 (T-stat ¼ 24.095, P ¼ 0.000). This result is in accordance with studies conducted by Raja et al (2018) and Lim et al (2019), who also found that TL has a positive effect on POF. According to Raja et al (2018), Transformational leaders are seen by their followers as trustworthy individuals who can provide support to create a feeling of security and comfort that allows employees to better adjust to an organization.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…TL is found to positively affect POF, as indicated by a positive path coefficient value of 0.752 (T-stat ¼ 24.095, P ¼ 0.000). This result is in accordance with studies conducted by Raja et al (2018) and Lim et al (2019), who also found that TL has a positive effect on POF. According to Raja et al (2018), Transformational leaders are seen by their followers as trustworthy individuals who can provide support to create a feeling of security and comfort that allows employees to better adjust to an organization.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in accordance with studies conducted by Raja et al. (2018) and Lim et al. (2019) , who also found that TL has a positive effect on POF.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations